A Formation Variation of the Median Nerve in the Arm - Fazlıoğulları, Zeliha; Ulusoy, Mahinur; Doğan, Nadire Ünver; Yılmaz, Mehmet Tuğrul; Karabulut, Ahmet Kağan (Fırat University, 2011)
The variation of the median nerve was observed incidentally during dissection of a 67 year-old male formalin-fixed Turkish cadaver assigned to the preclinical medical students at the Human Anatomy Laboratory of the Faculty of Meram Medicine, Selcuk University, Konya, Turkey. The median nerve was originating normally from the brachial plexus on proximal arm, but it received a communicating branch originated from the lateral cord on the middle arm. After lateral root of the median nerve leaved, the lateral cord bifurcated (lateral and medial branches) and both of them pierced the coracobrachial muscle. In previous studies, there were different definitions about connections. Knowledge of anatomic variations of the peripheral nervous system is helpful in explaining unusual clinical signs and permits correct interpretation of clinical neurophysiology.

Selçuk Üniversitesi Meram Tıp Fakültesi Anatomi Anabilim Dalı'nda rutin öğrenci diseksiyonları sırasında, 67 yaşındaki erkek kadavrada n. medianus varyasyonuna rastlandı. N. medianus kolun proksimalinde plexus brachialis'ten gelen dallarla normal olarak oluşmaktaydı. Kolun ortasında sinire fasciculus lateralis'ten gelen bir bağlantı dalının katıldığı tespit edildi. Radix lateralis nervi mediani ayrıldıktan sonra fasciculus lateralis'in ikiye ayrıldığı ve her iki dalın da musculus coracobrachialis'i deldiği gözlendi. Periferik sinir sisteminin anatomik varyasyonlarının bilinmesinin klinik nörofizyolojinin doğru yorumlanmasında ve farklı klinik bulguların açıklanmasında yararlı olacağı düşüncesindeyiz.
Kolda Nervus Medianus'un Bir Oluşum Varyasyonu